Mentor competencies and psychological mindsets in the context of a multinational corporation: an intervention-based study - Dreyer, Thomas Frederick (Central University of Technology, 2022)
Given the fiercely competitive international business environment, organisations need to actively engage in attracting, recruiting, and retaining top talent. Mentoring as a key part of talent management is pertinent, especially in the context of multinational corporations that employ diverse employees from across the globe. To that end, mentoring programmes help to improve organisational effectiveness. The purpose of this study was to contribute both theoretically and empirically to positioning mentoring as a key component of talent management in a multi-national corporation, namely Abu Dhabi National Oil Company (ADNOC) with specific focus on the ADNOC Gas Processing (AGP) business unit. Using a mixed-methods research approach, the study targeted 15 AGP mentors that were currently part of AGP’s mentoring team. Data was collected through pre- and post-self-assessment questionnaires and structured interviews were conducted to ascertain the thoughts and feelings of participants. A three-month mentor development journey was developed and implemented based on the findings of the pre-assessment phase of the study. The empirical results from the study indicated that prior to the mentor development journey, mentees admitted to having deficiencies in most mentor competencies and aspects relating to psychological mindsets. After undergoing the mentor development journey, the mentees acknowledged they had improved their competencies in these fields. A mentoring framework was designed with the aim of addressing the mentoring gaps. The key focus of the framework was to enhance trust between mentor and mentee, to enhance the mentor’s appreciation of the mentee’s growing independence, to promote communication between mentor and mentee, as well as to develop the empathic listening skills of mentors.
Thesis (Doctor: Human Resource Management)--Central University of Technology
Keywords: Mentor competencies; Psychological mindsets; Mentor development; Mentoring; Mentee; Talent management; United Arab Emirates